(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cybersecurity, often referred to as computer security, combines technology, procedures and practices to protect computers, networks, applications and data from attacks. The primary objective of cybersecurity is to prevent disruptions, software damage and data theft caused by hackers. This encompasses both physical and cyber security measures. Despite the efforts of numerous organizations and governments to combat cybercrimes through various strategies, significant concerns about cybersecurity persist. This essay explores the challenges that modern technology poses to cybersecurity and highlights the latest advancements, ethical considerations and trends that are reshaping the field.